Pemodelan kerugian finansial pada gempa bumi megathrust Sulawesi Utara berdasarkan ukuran risiko expected shortfall - Lengkas, Riski Ananda Putra; Azizah (Majalah Ilmiah Matematika dan Statistika, 2025)
Indonesia is one of the largest countries and is also the largest archipelagic country. Indonesia is also surrounded by large plates that cause eartquakes to occur very often. Earthquakes that occur cause financial losses that impact an area. This study aims to model the risk of financial losses due to the megathrust earthquake in North Sulawesi using the Earthquake Catastrophe (CAT) Model which has 4 modules consisting of hazard, inventory, vulnerability, and loss modules. This CAT Model allows structured analysis to identify potentian losses with the help of the Expected Shortfall (ES) risk measure. The result of this study indicate that 95th and 99th percentiles have large values, namely IDR 1,07 trillion and IDR 3,21 trillion. This finding indicates that the potential for extreme losses due to earthquakes in North Sulawesi is quite high, so risk mitigation is needed. Therefore, insurance companies need to allocate adequate reserves based on the expected shortfall risk measure and implement effective risk mitigation strategies. Keywords: CAT model, mega thrust earthquake, risk mitigation, expected shortfallMSC2020: 91G05